Kontaminasi Mikroplastik pada Perna viridis di Teluk Lampung - Zakiyah Rahim; Neviaty Putri Zamani; Meutia Samira Ismet (Jurnal Kelautan Tropis, 2022)
Fisheries activity in Lampung Bay which has been very active in recent years is the cultivation of green mussels (P. viridis) for consumption. Located in Teluk Betung Timur sub-district, this is considered appropriate because of the environmental parameters that support the life of P. viridis. The location of P. viridis cultivation is not far from coastal settlements (±500-600 m from settlements). Anthropogenic activities of coastal residents as well as the use of plastic materials in the cultivation are concerned to be the source of microplastic contamination that found in P. viridis. This study aims to determine the presence and characteristics of microplastics in P. viridis as well as to compare the abundance of microplastics in the gills and digestive organs. Taking 30 P. viridis by purposive sampling with homogeneous size. The samples were analyzed by microplastics in chemical oceanography and biology micro Laboratory, FPIK, IPB University. P. viridis tissue was destructed by using 10% KOH solution at a ratio of 1:3 (m/v) at 60 °C for 24 hours and then filtered using a 1.6 µm Whatman GF/A filter paper. Abundance of microplastics in whole soft tissue were 0.53±0.7 mgl/g. The gill organs were found to be more microplastic than the digestive organs (p<0.05). The fragments microplastic is most commonly found in intact tissues and digestive organs, while fiber is mostly found in the gills of P. viridis. Blue color and size <100 µm were most commonly found in intact tissues, gills and digestive organs of P. viridis.  Kegiatan perikanan di Teluk Lampung yang sangat aktif dalam beberapa tahun ini yaitu kultivasi kerang hijau (P. viridis) konsumsi. Berlokasi di kecamatan Teluk Betung Timur, hal ini dinilai tepat karena parameter lingkungan yang menunjang kehidupan P. viridis. Lokasi pembesaran P. viridis tidak jauh dari pemukiman penduduk pesisir (±500-600 m dari pemukiman). Kegiatan antropogenik penduduk pesisir juga penggunaan material plastik pada sistem pembesaran dikhawatirkan dapat menjadi sumber cemaran mikroplastik yang terdapat pada P. viridis. Penelitian ini bertujuan untuk mengetahui keberadaan dan karakteristik mikroplastik pada P. viridis juga membandingkan kelimpahan mikroplastik pada insang dan organ pencernaan. Pengambilan 30 P. viridis secara purposive sampling dengan ukuran homogen. Analisis mikroplastik dilakukan di laboratorium oseanografi kimia dan biologi mikro, FPIK, Universitas Pertanian Bogor. Destruksi jaringan P. viridis dengan menggunakan larutan KOH 10% perbandingan 1:3 (m/v) pada suhu 60 °C selama 24 jam lalu difiltrasi menggunakan filter paper whatman GF/A 1,6 µm. Mikroplastik tubuh kerang utuh yaitu 0,53±0,7 mgl/g. Organ insang lebih banyak ditemukan mikroplastik dibandingkan organ pencernaan (p<0,05). Bentuk fragmen paling banyak ditemukan di jaringan utuh dan organ pencernaan, sedangkan fiber banyak ditemukan di insang P. viridis. Warna biru dan ukuran <100 µm paling banyak ditemukan di jaringan utuh, insang maupun organ pencernaan P. viridis.